The healthy eating movement on social media and its psychological effects on body image - Zaharia, Alina; Gonța, Iulia (Frontiers in Nutrition, 2024)
IntroductionThe present study aims to investigate the relationship between social-media pressure, the tendency to internalize standards of beauty and attractiveness associated with thin bodies, which subsequently leads to distortion of body shape perceptions, and restrictive and emotional eating behavior disorders.MethodsA survey-based research design was employed, utilizing an online questionnaire to collect data. The study sample consisted of 614 students, selected from the most prestigious universities in Bucharest. The questionnaire incorporated validated scales measuring Socio-Media Pressure for a Thin Body Image (SMPTB), Body Appreciation (BA), Body Shape Perception (BSP), Restrained Eating Behavior (REB), and Emotional Eating Behavior (EEB).ResultsThe results confirmed the hypotheses of the research, meaning food restrictions are a way to diminish the level of dissatisfaction with body shape, to reduce the difference between the ideal body shape and the real one. Food restrictions are perceived as natural behaviors, appropriate to support the standards of beauty and attractiveness specific to this historical stage. Emotional eating disorders emerge as a way to compensate for the discomfort generated by low body esteem.DiscussionThe results underscore the pervasive influence of social media in shaping eating behaviors and body image perceptions. Food restrictions, framed as natural responses to societal pressures, highlight the need for interventions addressing the normalization of harmful beauty standards. Emotional eating behaviors reveal the psychological toll of body dissatisfaction, emphasizing the importance of strategies to foster positive body image and mental well-being. These findings provide a foundation for developing educational campaigns and therapeutic approaches targeting the psychological impact of social media on eating behaviors.